PERILAKU KONSUMEN PADA PEMBELIAN BERAS DI KOTA MAKASSAR (Cunsomer Behavior on Purchasing Rice in Makassar City) - Yulfirah Yusuf; A. Amrullah; A. Nixia Tenriawaru (Jurnal Sosial Ekonomi Pertanian, 2018)
One of the variables that cause differences in consumer behavior of rice is income. The purpose of this study is to identify the level of consumer income, rice attributes selected by consumers, and analyze the relationship between the level of consumer income with rice attributes. This research was conducted in Makassar City which is in traditional market of Pa'baeng-baeng and modern market of Lotte Mart. The object of research is the direct consumers who come shopping in the market Pa'baeng-baeng and Lotte Mart consists of 30 respondents respectively. The method of analysis is done by descriptive and Chi Square. The results show that the quality, packing, and price attributes are related to the income level. While the physical attributes of rice are not related to income levels.